The role of violence perpetration in driving externalizing problems and offending behavior among youth from eastern Democratic Republic of Congo. Issue 6 (1st September 2022) - Dumke, Lars; Haer, Roos; Zawadka, Annika; Salmen, Charlotte; Hecker, Tobias
Abstract: Youth in conflict‐affected regions are exposed to a multitude of traumatic events. These individuals often witness violence; experience it firsthand; and, in some cases, become perpetrators. The interplay of events shapes systematic trauma histories that may have unique implications for youths' mental health. In a cross‐sectional study conducted in eastern Democratic Republic of Congo (DRC), we interviewed 295 war‐affected youth (63.4% boys, M age = 16.70 years), including former child soldiers ( n = 171), regarding their traumatic experiences and mental health. Using latent class analysis, we identified four common trauma history classes categorized by (a) low exposure, (b) medium exposure, (c) high exposure, and (d) high exposure/perpetration. Across the sample, gradual increases in trauma load corresponded with increased vulnerability to posttraumatic stress disorder (PTSD) symptoms, ηp 2 = .36, and internalizing problems, ηp 2 = .12; however, only youth from the high exposure/perpetration class differed significantly from other youth in their levels of externalizing problems, ηp 2 = .13, and offending behaviors, ηp 2 = .17. A longer time in armed groups was related to a higher risk of both experiencing and perpetrating violence. The results indicate that it is not child soldier status, per se, but the perpetration of violence that reinforces a cycle of violence in conflict‐affected societies by contributing to increased externalizing problems and offending behaviors. In conflict regions, integrated approaches are needed to address both trauma and externalizing problems of war‐affected youth.